Brain network mechanism on cognitive control task in the elderly with brain aging: A functional near infrared spectroscopy study - Junjie Liang; Jiali Huang; Zhiwei Luo; Yuxi Wu; Lingxiong Zheng; Zengquan Tang; Wanying Li; Haining Ou; Haining Ou (Frontiers in Human Neuroscience, 2023)
ObjectiveTo study the brain network mechanism of cognitive control in the elderly with brain aging.Materials and methods21 normal young people and 20 elderly people were included in this study. Mini-mental State Examination and functional near-infrared spectroscopy (fNIRS) synchronous judgment test (including forward tests and reverse judgment tests) were performed on all subjects. To observe and compare differences in brain region activation and brain functional connectivity between subjects and forward and reverse trials by recording functional connectivity (FC) in different task paradigms and calculating bilateral prefrontal and primary motor cortical (PMC) areas.ResultsIn the forward and reverse judgment tests, the reaction time of the elderly group was significantly longer than the young group (P < 0.05), and there was no significant difference in the correct rate. In the homologous regions of interest (ROI) data, the FC of PMC and prefrontal cortex (PFC) in the elderly group was significantly decreased (P < 0.05). In the heterologous ROI data, except for left primary motor cortex (LPMC)-left prefrontal cortex (LPFC), the other PMC and PFC of the elderly group were significantly lower than the young group (P < 0.05) while processing the forward judgment test. However, the heterologous ROI data of LPMC-right prefrontal cortex (RPFC), LPMC-LPFC and RPFC-LPFC in the elderly group were significantly lower than the young group (P < 0.05) while processing the reverse judgment test.ConclusionThe results suggest that brain aging affected degeneration of whole brain function, which reduce the speed of information processing and form a brain network functional connection mode different from that of young people.